Kebijakan Pemerintah dalam Mengatasi Kenaikan Harga Beras di Indonesia - Sholikhah, Mar’atus; Anjani, Merita Dwi (Journal of Economics and Social Sciences (JESS), 2023)
Introduction: BPS recorded that Indonesia's inflation or Consumer Price Index (CPI) was 3.27 per cent in August 2023 annually, causing retail rice prices in August 2023 to increase by 1.43 per cent and rise by 13.76 per cent. This research aims to analyze government policies in dealing with rising rice prices in Indonesia in 2023. Research Methods: The method used is a qualitative method with a literature study approach. With types and sources of secondary data obtained from journals, the Central Statistics Agency and the National Strategic Food Price Information Center. Results: The results of this research show that to overcome this problem, the government is carrying out: 1.) importing rice from several rice-producing countries, 2.) ensuring rice reserves in Perum Bulog, 3.) carrying out market operations, 4.) holding a cheap food movement, 5.) Urge the public not to panic buying, 6.) Distribute 10 kilograms of rice aid to Beneficiary Families (KPM). Conclusion: Apart from these short-term policies, the government must also make long-term policies, such as increasing rice production and distribution.